2015
DOI: 10.1002/mabi.201500361
|View full text |Cite
|
Sign up to set email alerts
|

Designing Visible Light‐Cured Thiol‐Acrylate Hydrogels for Studying the HIPPO Pathway Activation in Hepatocellular Carcinoma Cells

Abstract: Various polymerization mechanisms have been developed to prepare peptide-immobilized poly(ethylene glycol) (PEG) hydrogels, a class of biomaterials suitable for studying cell biology in vitro. Here, we report a visible light mediated thiol-acrylate photopolymerization scheme to synthesize dually degradable PEG-peptide hydrogels with controllable crosslinking and degradability. We systematically evaluated the influence of immobilized mono-thiol pendant peptide on the crosslinking of these hydrogels. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Reverse transcription of isolated RNA (8–130 ng) into cDNA was achieved using PrimeScript RT reagent kit (Clontech). Gene expression level was assessed by quantitative real‐time polymerase chain reaction (PCR) on an Applied Biosystems 7500 fast real‐time PCR machine and analyzed following a published protocol . In short, samples were run at 95 °C for 30 s, followed by 45 cycles of 95 °C for 5 s, 55 °C for 30 s, and at 72 °C for 30 s. Within each experimental group, the detected levels of the genes of interest were normalized to the level of house‐keeping gene GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription of isolated RNA (8–130 ng) into cDNA was achieved using PrimeScript RT reagent kit (Clontech). Gene expression level was assessed by quantitative real‐time polymerase chain reaction (PCR) on an Applied Biosystems 7500 fast real‐time PCR machine and analyzed following a published protocol . In short, samples were run at 95 °C for 30 s, followed by 45 cycles of 95 °C for 5 s, 55 °C for 30 s, and at 72 °C for 30 s. Within each experimental group, the detected levels of the genes of interest were normalized to the level of house‐keeping gene GAPDH.…”
Section: Methodsmentioning
confidence: 99%
“…The thiyl radicals attack vinyl groups on PEGDA macromers to form carbonyl radicals and allow their propagation through other acrylates by chain-growth homopolymerization or by reacting with other thiols to allow step-growth addition, resulting in a mixed-mode step-chain growth polymerization mechanism ( Figure 1A) . The incorporation of thiol groups into PEGDA hydrogel imparts a thiol-etherester bond that makes bulk hydrolytic degradation possible and increases gel swelling ratio over time (Lin et al, 2015). The mechanism of PEGDA hydrogel gelation, stiffness, and degradation depend on several factors, including the concentrations of the NVP monomers and the CRGDS peptide.…”
Section: Mixed-mode Thiol-acrylate Reactionmentioning
confidence: 99%
“…However, a gradual decrease in the shear moduli is observed over time due to hydrolytic degradation. Previous studies have shown that the shear moduli of hydrogels are affected by the percentage of NVP macromers , Lin et al, 2015, Lee et al, 2014. Based on these studies, we chose 0.2% NVP peptide, which was shown to increase the viability and proliferation of hepatic cells over time .…”
Section: Thiol-acrylate Based Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations